Morphometric Characters Of Olive Ridley Turtle (Lepidochelys Olivacea) Hatching At Buggei Siata Beach, Betumonga Village, Mentawai Islands Regency. - Sababalat, Savni Retalia; Smanungkalit, Donopan; Damanhuri, Harfiandri; Suparno; Rusli, Mohd. Uzair (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2026)
The coastal waters of Indonesia are extensive, and one of the areas is the Mentawai Islands Regency. The Mentawai Islands are a distribution area for several types of turtles, including the leatherback turtle, green turtle, hawksbill turtle, and olive ridley turtle (Lepidochelys olivacea). The study focuses on the morphometric characteristics of olive ridley turtle hatchlings. Olive ridley turtles found in the Buggei Siata Turtle Conservation Area do not have complete morphometric data, so an observation of the morphometric characteristics of olive ridley hatchlings in this area was conducted. This study aims to determine the morphometric characteristics of olive ridley hatchlings and to complete the data for turtle conservation in Buggei Siata, Betumonga. The research was carried out from December 2021 to March 2022 at Buggei Siata Beach, Betumonga. The data analysis used ANOVA followed by Tukey's post-hoc test with 5 different nests and a total sample size of 35 hatchlings per nest. The results of the morphometric characteristics are as follows: carapace length (CL) ranged from 37.93 to 43.56 mm, carapace width (CW) from 28.36 to 36.35 mm, neck length (NL) from 10.08 to 14.21 mm, head width (HW) from 12.03 to 15.34 mm, front limb length (FLL) from 31.06 to 39.74 mm, plastron width (PW) from 19.74 to 29.85 mm, and weight from 13 to 18 grams. Significant differences were found between nests (p<0.05) in these measurements, while for head length (HL) from 16.98 to 19.91 mm, head height (HH) from 10.73 to 13.93 mm, rear limb length (RLL) from 11.37 to 21.88 mm, and plastron length (PL) from 23.86 to 37.21 mm, no significant differences were observed between nests (p>0.05). Based on the data, there are differences in the morphometric size of olive ridley hatchlings among the observed nests